Status, opportunities, and challenges of agroforestry practices: perspectives from Terhathum district, Nepal - Regmi, Gyanendra; Thapa, Utsab (Banko Janakari, 2023)
Tree cultivation in agricultural and public spaces serves as an alternative to fulfill the rural population's demand for forest products. However, agroforestry practices in Nepal, categorized by agro-ecological areas, lack sufficient documentation and improvement. The current investigation, undertaken in the Myaglung Municipality of Terhathum district in Nepal, aimed to examine the current practices and preferences related to agroforestry. The study also sought to uncover potential opportunities and challenges inherent in agroforestry while gauging the local community's perceptions regarding agroforestry. The primary data collection employed household interviews, key informant interviews, focus group discussions, and direct field observations while the secondary data were gathered from various public and unpublished sources. The farmers' preferences were evaluated using a five-point Likert Scale. In the study region, seven agroforestry systems, mainly employed for subsistence, were identified. The popular timber species in agroforestry included Alnus nepalensis, Schima wallichii, Castanopsis hystrix, C. tribuloides, and Pinus roxburghii. The favored fodder species were Ficus roxburghii, F. nemoralis, Artocarpus lakoochaa, Litsea monopetala, and Morus alba. On the other hand, the top fruit choices were Citrus reticulata, C. limon, Musa paradisica, Mangifera indica, and Litchi chinensis. The key barrier for agroforestry growth was the lack of technical knowledge in cultivating, managing, and harvesting agroforestry species, requiring attention for future agroforestry development in the region.